(untitled) (Journal of the College of Education for Women, 2019)
The study of sex Structure and age characteristics of an important element of thefollow-up changes between different population groups, which are connected to a large degreethe demographic, social and economic characteristics, particularly since each populationgroup varying characteristics in terms of age, sex entail social, demographic, cultural andeconomic implications, and from that the researcher has taken from Structure of sex and agefor population in the district of Tuz Khurmatu for (1997-2012 ) the subject of considerationand maintain compared to see the contrast between them. Qualitative Research for installationand the age of the urban and rural areas has touched the judiciary, as well as its respects.The study showed a contrast ratio kind in the district of Tuz Khurmatu between urban andrural areas and the province of Salahuddin according to 1997 census, with the percentage oftype in the judiciary (96 males per 100 females), which is lower than the amount of theprovince (98 male). And height according to the population estimates for the year 2012, withthe percentage of type in the judiciary (106.4 males per 100 females), which is higher than theproportion of the kind in the province and adult (105 male), and the record was attended byeliminating a remarkable rise in the proportion of the type of (108.5 male per 100 females),while it decreased in the countryside to reach (102 male). Can be explained by the migrationof males to urban areas, where diverse areas and employment opportunities compared to ruralareas, which determines the action only to agricultural activity. Forms Ahram population hasmade it clear to eliminate aspects of him as a young characterized as a very broad base andgradually Tenbj with sharp summit.